A rigorous user needs experience evaluation method based on software quality standards - Mohammad Zarour (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Our lives, nowadays, are digital. We, as humans, are using software applications in all our life aspects to meet our daily objectives and fulfill our needs. Software solutions that comprise mobile apps are widely spread, users can select from hundreds of available software solutions that fit their needs. Accordingly, user needs are becoming intricate and the software organizations are competing high to satisfy user requirements and the desires for better quality. This competition is not about satisfying the functional requirements but also satisfy user experience as well. Accordingly, studying, measuring, and improving user experience is crucial for the success of any software product. This research focuses on evaluating user experience needs by developing user experience needs evaluation method based on three main disciplines the user experience framework, the evaluation theory concept, and the ISOsoftware quality standards ISO/IEC 25022 and ISO/IEC 25023. Although these disciplines are available in the literature, they are not linked together to complete the mosaic picture of developing a UX evaluation method. Linking there three disciplines led to systematically identify the necessary evaluation criteria to evaluate user needs experience.